Endogenous hydrogen peroxide affects antidiuresis to cholinergic activation in the medial septal area - Sá, Jéssica Matheus [UNESP] (2019)
Cholinergic activation of the medial septal area (MSA) with carbachol produces thirst, natriuresis and antidiuresis. Hydrogen peroxide (H 2 O 2 ) injected into the medial septal area (MSA) impairs behavioral and renal responses induced by carbachol at the same site, suggesting the exogenous H 2 O 2 may modulate the responses to cholinergic activation in the MSA. In the present study, we investigated if the accumulation of endogenous H 2 O 2 in the MSA after the injection of the catalase inhibitor 3-amino-1,2,4-triazole (ATZ) also affects cholinergic responses. In addition, the effects of the combination of ATZ with a non-effective dose of H 2 O 2 in the MSA were also tested. Male Holtzman rats (280–320 g) with stainless steel cannulas implanted in the MSA were used. The treatment with ATZ (10 nmol) into the MSA partially reverted the antidiuretic effect of carbachol (10.5 ± 0.7, vs. saline + carbachol: 7.3 ± 0.6 ml/120 min), without changing carbachol-induced water intake (9.5 ± 1.9, vs. saline + carbachol: 10.7 ± 1.6 ml/60 min). The combination of a low dose of ATZ (2.5 nmol) with an ineffective dose of H 2 O 2 (0.5 μmol) into the MSA reduced carbachol-induced thirst (7.5 ± 2.0, vs. saline + carbachol: 14.9 ± 1.2 ml/15 min) and reverted the antidiuresis (8.1 ± 1.1, vs. saline + carbachol: 5.3 ± 0.9 ml/120 min). Sodium and potassium excretion were not modified regardless the treatment. Although exogenous H 2 O 2 injected in the MSA may affect most of the responses to cholinergic activation of the MSA, the antidiuresis is the response clearly modulated by endogenous H 2 O 2 .